The Sorcerer's Broom - Cassell, Eric J. (The Hastings Center report, 1993)
Like the broom in “The Sorcerer's Apprentice,” technologies take on a life of their own. To bring them under control, doctors must learn to tolerate ambiguity, resist the lure of the immediate, cease fearing uncertainty, and rechannel their response to wonder.